Special Needs of Boys and the Impact of Mixed-Gender Teams - Bernd Traxl; Johannes Huber (Ignatianum University Press, 2017)
Theoretically based on early pedagogical and psychoanalytic research findings, the Austrian W-INN-study aims at confirming research questions as well as finding possible new hypotheses about men's influence on children. The pilot study focuses on different research questions: What similarities and/or differences can be found in interactions with children depending on childcare staff composition (mixed gender vs. female)? What are childrens' (re-)actions in these groups/towards staff? Are there possible 'compensatory effects' of male childcarers for children who don't have much contact with fathers and/or men in general? Our paper will present the main results of the research project and its practical implications. Keywords: early childhood education - child-teacher-relationship - mixed gender staff - video observation - mixed-method-design